The direct and interactive effects of retail community engagement. (27th September 2021) - Lund, Donald J.; Hansen, John D.; Robicheaux, Robert A.; Cid Oreja, Clara
Abstract : Purpose: This paper aims to examine the direct and interactive effects of community engagement and economic value on customers' trust in, and commitment to, the retailer. This paper also examines the extent to which these variables, in turn, drive desirable behavioral outcomes in the form of positive word of mouth communications and share of customer. Design/methodology/approach: Study results are derived from a cross-sectional survey of 1, 757 respondents. Findings: The authors find that retailer community engagement positively impacts word of mouth and share of customer indirectly through commitment and trust. As hypothesized, the results support a suppressing interaction between community engagement and economic value on trust. Contrary to the hypothesis, the interactive effects on commitment are positive. Research limitations/implications: The study uses cross-sectional, single-sourced data. Incorporating secondary data or using experiments would reinforce these findings. This research is limited to local community engagement, future studies could broaden the focus to strategies that benefit communities outside the local area. Practical implications: Study results indicate that managers can indeed build stronger customer relationships through community engagement as customers are more apt to be trusting of and committed to retailers perceived to be more actively engaged in the community. These findings are particularly important considering that community engagement is typically less expensive than other marketing strategies. Community investments are inexpensive initiatives that retailers can leverage to generate a big impact in the hearts and minds of their customers. Originality/value: While it seems logical to assume that community engagement will benefit retailers in the form of stronger customer relationships, the authors empirically validate this assumption. The finding that community engagement simultaneously serves as both an antecedent and moderator is novel, albeit counterintuitive in the sense that the variable negatively moderates the economic value-trust relationship while positively moderating the economic value-commitment relationship. Taken in their totality, these findings indicate that community engagement serves to simultaneously drive stronger customer relationships while also differentially affecting the way customers arrive at their assessments.